PEMAKAIAN BAHASA JAWA DI LINGKUNGAN KRATON YOGYAKARTA: KAJIAN SOSIOLINGUISTIK - Oppie Meida Hidayani; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2019)
This study describes the form, function, and meaning of the use of Javanese in the Yogyakarta Palace environment. This type of research is a descriptive study with a qualitative approach. The research data are Javanese sentences. The data analysis method is the method of sharing with the dressing technique and is presented formally and informally. The results of the analysis of this study are (1) The form of Javanese language usage in the Yogyakarta Palace environment, which is based on word classes, such as interjection, noun, pronoun, verb, adverb, and particle. Based on greetings, such as greetings Mrs., Ca, Kanjeng, Dhik, and Mas. Based on the content, such as utterances containing offers and rejections, orders, questions and answers, notifications, and requests. (2) The function of using the Javanese language as a function of phatic, directive, metalingual, and emotive (3) The meaning of the use of Javanese language in the form of implicative meanings.